HEALTH LITERACY AND DIABETES RISK FACTORS SCORE - Fitria, Elis; Sylvia, Ester Inung; Datak, Gad (Proceedings of the International Conference on Applied Science and Health, 2019)
Introduction: Health literacy is an ability of people to get, process and understand the health information and services to make a health decision. Diabetes Mellitus (DM) is known as one of major health problem around the world. Decreasing the new cases of DM can be done by applying healthy lifestyle. Health literacy affects to people?s life style. This study aims to examine health literacy level of civil administration servant in Central Kalimantan with Diabetes risk factors score. Methods: Totally 42 respondents were recruited in this study. HLS-EU-Q16 was used to measure health literacy level and Finnish Diabetes Risk Score (FINDRISC) questionnaire was used to measure diabetes risk factors score. The data was analyzed in univariate and bivariate analysis used Chi-square. Results: Majority of respondents had aged under 45 years old (85.7%) and male (54.8%). The health literacy level of respondents was high (59.5%) and most of them had low risk of diabetes (69.0%). By using Chi-square, health literacy level was statistically significant with diabetes risk factors score (p=0.028). The risk factors for diabetes that mostly found were overweight, low physical activity, family history of diabetes and not consumed fruit and vegetables every day. Conclusion: Health literacy level was statistically significant with diabetes risk factors score. The government should promote healthy lifestyle to decrease the risk of getting non-communicable disease such as Diabetes Mellitus not only for civil servant but also general population.